EDUCATION, DIGITAL ACCESS, AND RURAL YOUTH EMPLOYMENT: EVIDENCE FROM MICRODATA IN MAGELANG REGENCY, INDONESIA - Muh Syaiful Bakhri; Rebecca Cindy Sartika; Firdan Thoriq Faza (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2026)
This study examines the determinants of youth employment in Magelang Regency, Indonesia, with a particular focus on the roles of education and digital access. Using microdata from the 2024 National Socio-Economic Survey (SUSENAS) and employing a binary logistic regression model, the analysis covers 560 individuals aged 15–29 years. The findings reveal that age significantly increases the likelihood of employment, suggesting that older youth are more likely to work due to accumulated experience and completed education. Female youth exhibit higher employment odds than males, reflecting the predominance of informal and home-based work among women in rural Magelang. In contrast, higher educational attainment negatively affects employment probability, indicating a mismatch between formal qualifications and the limited local labor demand for skilled workers. Urban residence positively influences employment chances, while marital status slightly reduces them, particularly among married women. Notably, internet access shows a negative and significant relationship with employment, implying that digital connectivity does not necessarily enhance job opportunities without productive and skill-oriented usage.